On the Origin and Significance of the Terms “Bovarism” and “Quixotism” - Mahmudova, Sevara (International Journal on Integrated Education, 2021)
The article explores the meaning of the terms “Bovarysme” and “Quixotism” based on the novels “Madame Bovary” written by French writer Gustave Flaubert and “The Ingenious Gentleman Don Quixote of La Mancha” by Spanish author Miguel de Cervantes. According to the author of the article, “Bovarysme” and “Quixotism” are similar concepts. They are an artistic image of dreamers who replaced unattainable dreams with their imaginations. Another meaning of the two works compared to these days is that they reflect the dreams of the people of those times, they also accurately reflect the gender characteristics of those reflected in dreams.